BENDING AFTER IMPACTKOMPOSIT SANDWICH BERPENGUAT SERAT BAMBU-FIBERGLASS DENGAN COREPOLYURETHANE RIGID FOAM - Catur, Agus Dwi; Sinarep, S.; Setyawan, Paryanto Dwi; Zainuri, Achmad; Supriadi, S. (Universitas Mataram, 2015)
Impact of the composite sandwich made of materials that become defect, how defects after impact in material need to be examined .Is that defected composites and wich still has the strength toremain in use?, then the bending after impact strength testing must be done to answer these questions.Composite sandwich with bamboo fiber-fiber glass reinforcement and with a core of 25mm rigid polyurethane foam sheet was produced. Composite sandwich made with two composite sandwich laminate as skinflanking the core. Laminated composite sandwich in this study varied number of layers of reinforcing fibers and type of fiber. Specimens subjected to drop weight impact with varying energy then defect researched and bending after impact strengthtested. Defects formed on the composite experiencing a drop weight impact loads are: delamination, basin and through hole. The more layers of reinforcing fibers in the composite skin causing moreshallowbasinformed by theresidualimpact. The greater the impact energy causes greater depth of residual basin. Composite sandwich still has the bending strength after impact. Residual bending strength decreases with increasing impact energy imposed on the composite.